2016
DOI: 10.24122/tve.a.2016.13.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Eldri starfmenn og yfirfærsla þekkingar í orkufyrirtækjum

Abstract: ÁgripMarkmið greinarinnar er að kynna rannsókn á því hvernig íslensk orkufyrirtaeki standa að yfirfaerslu þekkingar eldri starfsmanna til þeirra yngri áður en þeir fyrrnefndu haetta störfum. Efnið hefur lítið verið rannsakað hér á landi og er rannsókninni aetlað að baeta við fraeðilega umfjöllun á sviðinu, auka vitund fyrirtaekja um mikilvaegi yfirfaerslu þekkingar og til að stjórnendur geti nýtt niðurstöðurnar í starfi sínu. Rannsóknin byggðist á hálfstöðluðum viðtölum við 18 verk-og taeknifraeðinga og stjórn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 33 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…In view of Deaf people’s difficult experiences with the policies of oralism in the 19th and 20th centuries, the cultural–linguistic perspective assumes that Deaf individuals reject and oppose medical intervention. In this context, the Deaf community is defined as a minority group that demands recognition of sign language as a key element in the lives of individuals who define themselves as Deaf ( Stefánsdóttir, 2005 ).…”
Section: Being Deaf In the Context Of Increased Medical Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…In view of Deaf people’s difficult experiences with the policies of oralism in the 19th and 20th centuries, the cultural–linguistic perspective assumes that Deaf individuals reject and oppose medical intervention. In this context, the Deaf community is defined as a minority group that demands recognition of sign language as a key element in the lives of individuals who define themselves as Deaf ( Stefánsdóttir, 2005 ).…”
Section: Being Deaf In the Context Of Increased Medical Interventionmentioning
confidence: 99%
“…Although studies have shown that cochlear implants enable many, but not all, deaf individuals to learn spoken language ( Sharma et al., 2020 ; Spencer et al., 2012 ), research has suggested diverse experiences of deaf individuals with cochlear implants when it comes to their identities. Cochlear implants have been controversial from the beginning within Deaf communities, and the intervention has been described by some as a continuation and reinforcement of oralism ( Stefánsdóttir, 2005 ). According to Lane and Bahan (1998 ), cochlear implants reflect the “hearing norm”, that is, that everyone should hear and speak.…”
Section: Context Of Deafness Under the Influence Of Technological Changementioning
confidence: 99%
See 1 more Smart Citation